Coronavirus concept research through psycholinguistic lenses - Goroshko, Olena (My University, 2020)
The article reveal the perception of the concept of "coronavirus" in the linguistic consciousness of native speakers of Ukrainian. Using the method of free association test, ten associative fields to the words describing the concept of coronavirus: "Coronavirus, Covid-19, pandemic, social distance, lockdown quarantine, mask, tests, self-isolation, vaccine" are obtained. The data provide the clear picture with what the coronavirus concept associates in the mentality of Ukrainians. The negative stimuli linked with danger, uncertainty and illness are prevailed.
Дослідження концепту "пандемія коронавірусу" за допомогою психолінгвістичного інструментарію
Keywords: coronavirus concept; free associative test; mentality; Ukrainian